Cysteine‐rich protein 61 regulates the chemosensitivity of chronic myeloid leukemia to imatinib mesylate through the nuclear factor kappa B/Bcl‐2 pathway. Issue 8 (18th June 2019) - Song, Yanfang; Lin, Qing; Cai, Zhaolian; Hao, Taisen; Zhang, Yaohan; Zhu, Xianjin
Abstract: Although the targeted tyrosine kinase inhibitor imatinib mesylate (IM) has achieved significant responses against CML in the clinical setting, a small proportion of patients fail to respond to IM treatment and their disease continues to progress, indicating resistance to IM therapy. As a secreted extracellular matrix protein, cysteine‐rich protein 61 (Cyr61) plays an important role in the resistance of solid tumors to chemotherapy, but its role in CML is unclear. In the present study, we observed that Cyr61 levels were upregulated in the plasma and bone marrow (BM) of patients with CML as well as in K562 cells. This upregulation of Cyr61 significantly decreased IM‐induced cellular apoptosis of K562 cells through nuclear factor kappa B/B‐cell lymphoma 2 pathways. Inhibition of Cyr61 restored the chemosensitivity of K562 cells to IM both in vitro and in vivo. Thus, our results showed for the first time that Cyr61 plays an important role in regulating the chemosensitivity of CML cells to IM, suggesting that selectively targeting Cyr61 directly or its relevant effector pathways may provide potential value in improving the clinical response of patients with CML to IM treatment. Abstract : Cyr61 levels were upregulated in the plasma and BM of patients with CML as well as in K562 cells. This upregulation of Cyr61 significantly decreased IM‐induced cellular apoptosis of CML cells. Thus, our results suggest that selectively targeting Cyr61 directly or its relevant effector pathways may provide potential value in improving the clinical response of patients with CML to IM treatment.